2021
DOI: 10.1038/s41598-020-80616-3
|View full text |Cite
|
Sign up to set email alerts
|

Pure thermal spin current and perfect spin-filtering with negative differential thermoelectric resistance induced by proximity effect in graphene/silicene junctions

Abstract: The spin-dependent Seebeck effect (SDSE) and thermal spin-filtering effect (SFE) are now considered as the essential aspects of the spin caloritronics, which can efficiently explore the relationships between the spin and heat transport in the materials. However, there is still a challenge to get a thermally-induced spin current with no thermal electron current. This paper aims to numerically investigate the spin-dependent transport properties in hybrid graphene/silicene nanoribbons (GSNRs), using the nonequili… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 92 publications
1
9
0
Order By: Relevance
“…The thermoelectric performance of nanostructures can also be enhanced by various ways, such as hybridization 31 , 32 , defects 33 35 , and doping 36 , 37 . As shown in the previous studies 4 , 38 , 39 , the hybrid nanostructures theoretically show superior thermoelectric properties than the similar materials with the single nanostructures. Several studies have already been performed to investigate various properties of the GSNRs in which GE and SE have vertically or laterally bonded together 40 43 .…”
Section: Introductionsupporting
confidence: 66%
See 1 more Smart Citation
“…The thermoelectric performance of nanostructures can also be enhanced by various ways, such as hybridization 31 , 32 , defects 33 35 , and doping 36 , 37 . As shown in the previous studies 4 , 38 , 39 , the hybrid nanostructures theoretically show superior thermoelectric properties than the similar materials with the single nanostructures. Several studies have already been performed to investigate various properties of the GSNRs in which GE and SE have vertically or laterally bonded together 40 43 .…”
Section: Introductionsupporting
confidence: 66%
“…The results showed that the combination of GE with other 2D materials could lead to a hybrid structure with various properties and applications 44 47 . Nevertheless, there are little data about the electronic behavior, spin transport, and thermoelectric attributes of the GSNRs 38 , 46 , and further research is still required in this area.…”
Section: Introductionmentioning
confidence: 99%
“…4–7 Clearly, spin caloritronics provides an alternative strategy for waste heat recovery and low-power consumption technology. 8,9 To date, many investigations have demonstrated that various candidates, such as single molecular magnets, metallic clusters, zigzag silicene and graphene nanoribbons, hybrid graphene/silicene nanoribbons, and magnetic tunneling heterojunctions, 10–17 hold great promise in spin caloritronics. 18 For example, due to the proximity effect, Gholami et al reported that the pure thermal-driven spin current through hybrid graphene/silicene nanoribbons can be modulated via changing the temperature bias, and then predicted the nearly perfect spin-filtering effect and the negative differential thermoelectric resistance.…”
Section: Introductionmentioning
confidence: 99%
“…18 For example, due to the proximity effect, Gholami et al reported that the pure thermal-driven spin current through hybrid graphene/silicene nanoribbons can be modulated via changing the temperature bias, and then predicted the nearly perfect spin-filtering effect and the negative differential thermoelectric resistance. 15…”
Section: Introductionmentioning
confidence: 99%
“…We also analyze the effect of the Rashba field, showing that it enhances the cooling effects in the valence band. The generic existence of spin-polarized TMD electronic states given by TRS breaking that can be accessed by gating, suggests that these hybrid systems could be used as tunable thermal spin filters [37] for functional applications.…”
mentioning
confidence: 99%